Workforce Digital Capability and Service Delivery Sustainability among Universities in Ilorin, Kwara State, Nigeria - Olodo, Hameedat Bukola; Aremu, M. A.; Balogun, S. A. (NIU Journal of Management Sciences, 2026)
Organisations are increasingly relying on digital technologies to support communication, operational activities, and service delivery processes, but despite substantial investments in digital technologies, many organisations continue to encounte service disruptions, inefficient work processes, under-utilisation of digital systems, and inconsistent service outcomes. These persistent challenges suggest that the availability of digital technologies alone may not guarantee sustainable service delivery, highlighting the need to examine workforce-related factors that influence the effective use of digital resources. This study therefore examined the effect of workforce digital capability on service delivery sustainability, with particular focus on workforce digital skills and workforce adaptability. A cross-sectional survey design was adopted for the study and data were collected from 340 academic and non-academic staff members of selected universities in Ilorin, Kwara State, using a structured questionnaire. The data were analysed using multiple regression analysis. The findings of the study revealed that workforce digital skills significantly influenced service delivery sustainability (F = 202.60, p < 0.05), accounting for 64.3% of the variation in service delivery sustainability (R² = 0.643). Specifically, digital literacy, digital communication skills, and digital problem-solving ability had significant positive effects on service delivery sustainability. Similarly, workforce adaptability significantly influenced service delivery sustainability (F = 157.66, p < 0.05), explaining 58.4% of the variation (R² = 0.584). Technological adaptability, continuous learning orientation, and work process flexibility were also found to have significant positive effects on service delivery sustainability. The study concluded that digital skills and adaptability are critical resources for maintaining efficient, reliable, and sustainable service delivery in digitally evolving organisations. The study recommended continuous digital training, workforce upskilling, and adaptability development initiatives to enhance long-term service delivery performance. Keywords: Workforce, Digital Capability, Service Delivery, Sustainability